2015
DOI: 10.2106/jbjs.n.00426
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Ankle Arthrodesis and Adjacent-Joint Arthritis in the Hindfoot

Abstract: There is no true consensus in the literature as to the effects of ankle arthrodesis on biomechanics or whether ankle arthrodesis leads to adjacent-joint arthritis. Similarly, a correlation between postoperative imaging findings and clinical presentation in this cohort of patients has not been conclusively demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 36 publications
0
59
0
4
Order By: Relevance
“…A recent systematic review by Ling et al . of gait‐analysis studies, biomechanical studies and clinical studies has not concluded definitively whether there is any clear correlation between ankle arthrodesis and adjacent‐joint degeneration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Ling et al . of gait‐analysis studies, biomechanical studies and clinical studies has not concluded definitively whether there is any clear correlation between ankle arthrodesis and adjacent‐joint degeneration .…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that patients who required arthrodesis of the ankle joint often had changes in the mid and hindfoot, particularly the subtalar joint before ankle arthrodesis had been performed [45]. A recent systematic review by Ling et al of gait-analysis studies, biomechanical studies and clinical studies has not concluded definitively whether there is any clear correlation between ankle arthrodesis and adjacent-joint degeneration [46].…”
Section: Typementioning
confidence: 99%
“…Nevertheless, Ebalard et al reported that 84% of patients complained of pain after a minimum follow-up of 10 years (13). In other studies, the prevalence of osteoarthrosis ranged from 24-100% in the subtalar joint and from 18-77% in the Chopart joints (14).…”
mentioning
confidence: 96%
“…A recent systematic review by Ling et al[86] investigated the relationship between ankle arthrodesis and adjacent-joint arthritis and demonstrated that there was insufficient evidence to support either that ankle arthrodesis caused adjacent-joint arthritis or that pre-existing joint arthritis could have already existed in those cohort of patients. As the current postulation include that there may be inherent pre-existing adjacent joint arthritis in the majority of patients requiring fusion, no clear consensus can be made on whether ankle arthrodesis can cause or predispose to hindfoot arthritis.…”
Section: Outocomes After Ankle Arthrodesis: a Systematic Reviewmentioning
confidence: 99%